2010
DOI: 10.1007/s00213-010-1988-3
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cannabis users show altered neurophysiological functioning on Stroop task conflict resolution

Abstract: These findings indicate that chronic use of cannabis may impair the brain's ability to respond optimally in the presence of events that require conflict resolution and hold implications for the ability to refrain from substance misuse and/or maintain substance abstention behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 53 publications
(77 reference statements)
4
61
0
Order By: Relevance
“…Chronic, heavy marijuana smokers have previously demonstrated impaired performance on both the Stroop and WCST relative to control participants (Battisti et al, 2010;Fontes et al, 2011;Gruber et al, 2012b;Lane et al, 2007), and prior work has noted that early-onset marijuana smokers accounted for the between-group differences across multiple cognitive domains (Ehrenreich et al, 1999;Fontes et al, 2011;Gruber et al, 2012b;Pope et al, 2003). Those findings, combined with results from the current study, highlight the importance of examining age at onset of marijuana use.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Chronic, heavy marijuana smokers have previously demonstrated impaired performance on both the Stroop and WCST relative to control participants (Battisti et al, 2010;Fontes et al, 2011;Gruber et al, 2012b;Lane et al, 2007), and prior work has noted that early-onset marijuana smokers accounted for the between-group differences across multiple cognitive domains (Ehrenreich et al, 1999;Fontes et al, 2011;Gruber et al, 2012b;Pope et al, 2003). Those findings, combined with results from the current study, highlight the importance of examining age at onset of marijuana use.…”
Section: Discussionsupporting
confidence: 71%
“…Our results complement previous research using both correlation and regression analyses to address the role of marijuana use variables. Earlier age at marijuana onset has previously been shown to correlate with impaired performance on the Stroop and WCST tasks (Battisti et al, 2010;Gruber et al, 2012b), whereas increased frequency and magnitude of marijuana use have been shown to be related to impairment in psychomotor speed, sustained attention, and cognitive inhibition (Lisdahl & Price, 2012), as well as verbal memory (Solowij et al, 2011) and executive function (Gruber et al, 2012b;Harvey et al, 2007). In addition, this study incorporated logistic regression techniques and demonstrated that increased total perseverative errors on the WCST is a moderately accurate predictor of marijuana smokers, suggesting that this may be a clinical characteristic of chronic, heavy marijuana use.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, chronic cannabis users perform less well than healthy peers on measures of memory, information processing, and cognitive control (eg, Schreiner and Dunn, 2012;Solowij et al, 2002, but also see Takagi et al, 2011). Further, compared with non-drug-using adults, cannabis users often exhibit lower neural activity during performance on memory, learning, and cognitive-control tasks (including the Stroop color-word interference task) across several brain regions, including prefrontal cortex (Battisti et al, 2010;Eldreth et al, 2004;Gruber and Yurgelun-Todd, 2005, but c.f., Harding et al, 2012).…”
Section: Introductionmentioning
confidence: 99%